Penerapan Lima Prinsip Dasar Pesantren Tebuireng dalam Membentuk Karakter Santri di Pesantren Tebuireng Jombang - Isnan Badarudin Kamal (Jurnal Dirosah Islamiyah, 2024)
The Five Basic Principles of the Tebuireng Islamic Boarding School is the main motto used by the Tebuireng Islamic Boarding School in implementing the character of its students. These five characters are a summary of the seventh supervisor of the Tebuireng Islamic Boarding School (KH. Salahuddin Wahid) which he took from one of the books written by Hadratus Shaykh KH. Muhammad Hasyim Asy;ari, namely in the book "Adabul 'Alim wal Muta'alim". The five characters are 1) Sincerity, 2) Honesty, 3) Responsibility, 4) Hard work, 5) Tolerance. The focus of this research is: 1) the concept of the five basic principles of the Tebuireng Islamic Boarding School, 2) the application of the five basic principles of the Tebuireng Islamic Boarding School to the character formation of students, 3) supporting and inhibiting factors in the application of the five basic principles of the Tebuireng Islamic Boarding School. In this research, the author uses a qualitative type of research with a case study research approach. Data was collected using three techniques, namely: 1). Interview. 2). Observation, 3). Documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. Data validity checking techniques use several things including: extending participation and triangulation.The results of this research are: 1). The application of the Five Basic Principles of Tebuireng is one of the strategies used in education to shape the character of students. The administrators and supervisors carry out their duties in accordance with the main tasks and functions that have been determined by the Islamic boarding school, providing understanding and evaluation to the students is the main factor in success in forming the character of the students, 2). The application of the Five Basic Principles of Tebuireng in forming the character of the students is based on the room supervisor system, then strengthened by the boarding school administrators and supported by bandongan studies by the caregivers using the book "Adabul 'Alim wal Muta'alim", 3). Supporting factors in the implementation of the Five Basic Principles of Tebuireng are the role of Islamic boarding school caregivers who review and explain in detail the source books of the founder of Tebuireng Islamic boarding school, as well as the system of guiding one person in each room. Meanwhile, the inhibiting factors are the existence of several supervisors who have different ideas in implementing the room program and the lack of maximum performance by several supervisors in carrying out the main duties and functions of the Islamic boarding school